Integration of Local Wisdom-Based Deep Learning PCTS Model to Enhance Students' Critical Reasoning, Creativity, and Collaboration - Faidin, Faidin; Suharti, Suharti; Panji Suwiryo, Adhitya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The 21st century demands critical reasoning, creativity, and collaboration skills as essential competencies for facing modern challenges. However, current history learning still faces obstacles such as the lack of integration of local wisdom and monotonous learning methods, resulting in low student performance in these areas. The urgency of this research is to develop an effective learning model that combines deep learning and local wisdom to improve students' 21st-century skills. This study aims to examine the effect of integrating the PCTS (Problem-Centered Thinking Skill) Deep Learning Model based on local wisdom on improving students' critical reasoning, creativity, and collaboration. The method used was a quasi-experimental design with a Nonequivalent Control Group design involving 74 students divided into experimental and control groups. Data were collected through tests, questionnaires, observations, and interviews, then analyzed descriptively and using t-tests. The results showed a significant increase in mean gain in the experimental group for critical reasoning (8.19 vs. 3.20), creativity (8.19 vs. 3.58), and collaboration (8.06 vs. 3.56) compared to the control group, with a significance value of p = 0.000. Teachers implemented a project-based and collaborative participatory learning model despite facing technological challenges and teacher preparedness. The conclusion of this study confirms that the integration of the PCTS Deep Learning Model based on local wisdom effectively improves students' 21st-century skills in history learning.